BRAZILIAN SOUTH REGION PROFESSIONAL SOCCER PSYCHOLOGISTS: OPINIONS ABOUT AGGRESSIVENESS (Fiep Bulletin - online, 2014)
The present study aimed to collect, among sports psychologists that worked in Brazilian south region professional soccer clubs during 2004, their opinions about aggressiveness in soccer. Using questionnaire and interviews, it was possible to infer that: a) the most employed aggressiveness technique containment is the visualization; b) feedback is the most employed after-game technique by these professionals; c) the majority of the participants believes that professional soccer has more instrumental than affective aggression; d) the majority believes that players know the rules of the game, but it is worth to study them better; e) the social learning theory about aggressiveness is the most accepted between the participants. It is suggested that new researches collect these professionals' opinions, because they live deeply in the Sports Psychology practice, and it would complement its theoretical mainframe.
Keywords: Sports Psychology; soccer; aggressiveness